2010
DOI: 10.1111/j.1538-7836.2010.03852.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal bleeding in patients receiving anticoagulant therapy for venous thromboembolism: findings from the RIETE registry

Abstract: Summary.  Background: Fatal bleeding is a serious consequence of anticoagulant therapy, but factors associated with fatal bleeding during the first 3 months of treatment of venous thromboembolism (VTE) are uncertain. Methods: Using data from RIETE, an ongoing registry of consecutive patients with acute VTE, we assessed risk factors for fatal bleeding among all patients. We then used this information to derive a clinical model that would stratify a patient’s risk of fatal bleeding during the first 3 months of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
124
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(133 citation statements)
references
References 18 publications
3
124
2
4
Order By: Relevance
“…Our data confirm that the use of anticoagulant therapy carries a higher risk to bleed than to recur in the elderly and in the renally impaired, as previously reported 14, 21, 22, 23, 24, 25. During initial therapy with LMWH, fragile patients weighing ≤50 kg received slightly higher (non‐significantly) mean daily doses per body weight of LMWH compared with non‐fragile patients.…”
Section: Discussionsupporting
confidence: 88%
“…Our data confirm that the use of anticoagulant therapy carries a higher risk to bleed than to recur in the elderly and in the renally impaired, as previously reported 14, 21, 22, 23, 24, 25. During initial therapy with LMWH, fragile patients weighing ≤50 kg received slightly higher (non‐significantly) mean daily doses per body weight of LMWH compared with non‐fragile patients.…”
Section: Discussionsupporting
confidence: 88%
“…Guidelines generally suggest a minimum of 3 months, a length of treatment that is associated with a lower risk of VTE recurrence than shorter durations [46], or long term if the initial event was idiopathic or if risk factors persist (table 4) [2,12,46,[50][51][52][53]. Patients with CTEPH should remain on lifelong anticoagulation [54].…”
Section: Long-term Prevention Of Recurrent Vte After An Initial Pementioning
confidence: 99%
“…Judging the benefit of continued anticoagulation in elderly patients, those with severe renal impairment, patients with cancer or those who are immobilised is particularly challenging because these factors increase the risks of both recurrent VTE and serious anticoagulant-related bleeding [12,51,52]. Of note, a population-based case-control study showed that patients with cancer receiving chemotherapy have an approximately six-fold increase in the adjusted (for location at VTE onset) risk ratio for VTE compared with healthy controls [55].…”
Section: Long-term Prevention Of Recurrent Vte After An Initial Pementioning
confidence: 99%
“…Fatal major bleeding occurs in 0.2% of patients within 3 months after PE, with a nonfatal major bleeding rate of 2.0% [9,10]. Before outpatient treatment in low-risk PE patients can be accepted as standard patient care, comparable safety to inpatient care has to be proven [11].…”
Section: Introductionmentioning
confidence: 99%